Panel Method in Hedging: Evidence from The Indonesian Agricultural Sector - Faizul Mubarok; Risma Nadya Utami (Jurnal Dinamika Akuntansi)
Hedging is a derivative instrument in the form of actions used to minimize risks due to fluctuations in foreign currencies, interest rates, and commodity prices. This study aims to analyze the factors that influence hedging in agricultural sector companies using the panel data method in the form of quarterly from 7 companies from 2013 to 2019. The study results show growth opportunity, financial distress, debt, leverage, firm size, liquidity, profitability, and dividend payout ratio significantly influence the use of hedging. This study's results indicate that agricultural sector companies as a whole use hedging to protect against future risk exposures. Besides, it is necessary to know the factors that influence making decisions using hedging. This study recommends that companies increase export productivity balanced with appropriate hedging policies to improve company performance.